Studi Potensi Resiko Tanah Lunak dalam Pembangunan Ibu Kota Negara dengan Ajuan Penanganan Menggunakan Metode Prefabricated Vertical Drain Berbahan Alami - Arianto, Benny (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2020)
The Capital City of Indonesia will be moving to East Kalimantan Province soon. However, based on previous research and cases, the area around the National Capital (IKN) has potentially soft soil problem. Field and laboratory investigations revealed that in the area around IKN there was soft soil as indicated by the results of the cone penetrometer tests which generally, have resistance values of less than 10 kg/cm2. Moreover, the investigation also shows the existence of swelling soil, land movement, liquefaction, and illitic soil with medium to medium activity. This research is a literature study using secondary data to propose techniques to overcome the potential of soft soils in IKN. Preloading method with Prefabricated Vertical Drain (PVD) is a method that has been used in overcoming soft soils in several infrastructure developments in Kalimantan. However, the results of laboratory tests and field tests of several previous researchers have produced that conventional PVD material in the form of polymers can be replaced with natural fiber materials from jute and coconut fibers. It is more environmentally friendly and effective than conventional PVD. The use of this technique supports the vision of IKN development: Smart, Green, Beautiful, and Sustainable.